(untitled) (World Bulletin of Management and Law, 2023)
The implementation of International Financial Reporting Standards (IFRS) in Uzbekistan has presented both challenges and opportunities for the accounting profession. This article examines the impact of IFRS adoption on the accounting profession in the country, identifying key challenges faced by accounting practitioners and exploring potential opportunities for professional development and growth. The findings suggest that, while IFRS adoption has created challenges related to the need for training, changes in accounting practices, and regulatory compliance, it has also provided opportunities for improved transparency, enhanced international credibility, and access to global markets